Adaptation and Validation of The Achievement Emotions Questionnaire Academic Boredom Subscale in Indonesian Islamic Boarding Schools - Affandi, Ghozali Rusyid; Hadi, Cholichul; Fardana, Nur Ainy; Rahman, Mohd Nazri Bin Abdul (Islamic Guidance and Counseling Journal, 2025)
Despite the growing recognition of academic boredom as a factor influencing student engagement and achievement, there is still a lack of culturally adapted and validated instruments for use in religious and highly structured educational settings such as Islamic boarding schools. Most existing tools were developed in general, non-boarding, and secular school contexts, primarily in Western countries that differ significantly from the cultural and educational characteristics of Islamic boarding schools in Indonesia. Therefore, this study aimed to adapt and test the validity and reliability of the 16-item Academic Boredom subscale of the Achievement Emotions Questionnaire (AEQ) among Islamic boarding school students in Indonesia. A total of 408 students from Islamic Boarding Schools in East Java, Indonesia participated in the study. This process adaptation involved several stages, including double translation, expert review, a readability test and construct confirmation. The data were analysed using Confirmatory Factor Analysis (CFA) with the Diagonally Weighted Least Squares (DWLS) method, as well as with reliability tests using Cronbach's Alpha and McDonald's Omega. The model fit indices (CFI = 0.919; TLI = 0.901; RMSEA = 0.071) and high internal consistency (α = 0.906; ω = 0.917) indicate that the adapted Academic Boredom subscale is valid and reliable for use in Islamic boarding school students in Indonesia. The implications of the study indicate that the adapted AEQ scale can be used as a diagnostic assessment tool for academic boredom in Islamic boarding school-based junior high school student, as well as supporting the development of affection-based learning interventions in Islamic Boarding School.